Pengaruh Edukasi Media Booklet Terhadap Kepatuhan Diet Pada Penderita Diabetes Melitus Tipe 2 Di Wilayah Kerja Puskesmas Ranomuut - Rosilawati Tan; I Made Rantiasa; Sarwan Sarwan (Vitamin : Jurnal ilmu Kesehatan Umum, 2023)
Diabetes Mellitus is a group of metabolic diseases characterized by hyperglycemia due to impaired insulin production, insulin action. Management of the 4 pillars of diabetes mellitus includes education on eating arrangements. The purpose of this study was to determine the effect of booklet media education on dietary compliance in patients with type 2 diabetes mellitus in the ranomuut health center work area.The research design used is a pre-experiment with a one group pre and posttest design approach. The sample in this study were 23 respondents using purposive sampling technique. the research instrument used was a questionnaire sheet. Then the data that has been collected is processed using the SPSS 16.0 program to be analyzed using the Mc.Nemar statistical test with a level of meaningfulness (α) = 0.05. Based on the results of the study when given education for the pre-test, the highest percentage was non-compliant 21 respondents (91.3%) and the post-test the highest percentage was compliant 22 respondents (95.7%). From the results of the Mc.Nemar statistical test, the P value = 0.000 with a significance of <0.05, which means Ha is accepted and Ho is rejected. The conclusion of this study is that there is an effect of booklet media education on dietary compliance in patients with type 2 diabetes mellitus in the ranomuut health center work area. This study is expected to increase knowledge in implementing dietary compliance so that it can control the problem of diabetes mellitus.